Developing Mechanism of Ensuring Enterprise Economic Security at Time of Introducing Digital Technologies - I. V. Manakhova; E. V. Levchenko; A. V. Bystrov; A. R. Esina (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
Introduction of digital technologies causes transformation of all mechanisms of enterprise management. On the basis of processing and systematization of theoretical and practical and applied works by Russian and overseas researchers and reports of official statistics the authors study specific features of the process of ensuring economic security (ES) in conditions of digitalization, analyze and systematize the lines in its development and show ways of further upgrading. The lines in developing mechanisms of ES ensuring lie in the field of available tools, methods of risk estimation and threat identification, indicators and coefficients of the economic security level, supporting subsystems, including personnel, legal, informational and managerial systems. Upgrading the system of risk estimation can be carried out in view of criteria of their identification. Within the frames of the research the authors showed specific risks of economic security arising in the process of digitalization of company management: inadequacy of digital infrastructure, insufficiency of digital tools, undeveloped digital competences. The principle internal risks of economic security are misunderstanding of digital transformation concept at the top management level and the gap in digital development of employees. The authors think that improvement of mechanisms of the enterprise ES is connected with raising the level of technical, informational and program support, the level of employees’ competences.